2018
DOI: 10.1111/joor.12725
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of nasal airway stent (Nastent) on obstructive sleep apnoea and prediction of treatment outcomes

Abstract: Summary Background Obstructive sleep apnoea (OSA) is characterised by recurrent episodes of partial or complete upper airway collapse during sleep and is highly prevalent in the general population. The nasopharyngeal airway stent (Nastent) is a specifically designed, preformed silicone tube that intends to maintain the upper airway patency during sleep and reduce snoring and sleep apnoea. Objective(s) The purpose of this study was to determine the efficacy of Nastent treatment and examine predictors for Nasten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Previous studies have shown that the NAS can reduce the AHI scores of patients without OSAS surgery [19, 26]. However, these studies had a small number of participants and long-term effects were not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the NAS can reduce the AHI scores of patients without OSAS surgery [19, 26]. However, these studies had a small number of participants and long-term effects were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The Mallampati classification is an established method for assessing the pharynx status [31]. Interestingly, a previous study has used it to evaluate the NAS effect on the pharynx status [26]; therefore, we decided to use the Mallampati classification in the present study. We demonstrated that patients with Mallampati class II tended to show more improvements after using the NAS compared to the other Mallampati classification groups.…”
Section: Discussionmentioning
confidence: 99%
“…The tube is inserted transnasally with the intention of stenting the palatal velum (Figure 1(b)–(d)) to reduce snoring, hypopneas, or apneas. 4…”
Section: Methodsmentioning
confidence: 99%
“…Okuno et al. 4 demonstrated a significant reduction in snoring and the respiratory disturbance index (RDI) using a nasopharyngeal stent (Naśtent; Corinium Medical Equipment Ltd., Cirencester, UK). They also demonstrated an association between responders and a narrow velopharynx in cephalography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation